Detection and quantification of heavy metals and minerals in poultry feed collected from selected local markets in Bangladesh - Islam, Md Khirul; Sachi, Sabbya; Quadir, Quazi Forhad; Sikder, Mahmudul Hasan; Faruque, Muhammad Omar; Miah, Mohammad Alam; Islam, Md Shafiqul; Sani, Arif Hossen; Baishya, Pollab; Rafiq, Kazi (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study was primarily conducted to assess the stakeholders’ knowledge regarding the contamination caused by heavy metals in poultry feedstuffs. The concentration of some heavy metals (lead, chromium, cadmium, and nickel) and macro-minerals (sodium, potassium, and calcium) was also analyzed in poultry feeds collected from selected local markets in Sherpur district, Bangladesh. Materials and Methods: A well-structured questionnaire survey was used to investigate different stakeholders’ perspectives in relation to metal contamination in feed. Heavy metals and calcium were determined by atomic absorption spectrophotometry. The flame emission spectrophotometric technique was applied to determine sodium and potassium. Results: The majority of the stakeholders (90%) were found to have no knowledge regarding heavy metal contamination. Lead and nickel concentrations were below the detectable level in the collected samples. The average concentration of chromium in Jhenaigati upazila was four times higher than in Nalitabari upazila, at 21.806 mg kg−1 and 5.452 mg kg−1, respectively. The concentrations of cadmium in both brand and nonbrand samples exceeded the maximum allowable limit set by the European Union at 1.329 mg kg−1 and 1.328 mg kg−1, respectively. Sodium, potassium, and calcium were found in the ranges of 0.0011%–0.0035%, 0.0010%–0.0013%, and 0.0080%–0.0305%, which were extremely low in concentration compared to the minimum requirement in poultry feed. Conclusion: Regular surveillance and governance systems should be incorporated into national policy to cease the hazardous impacts of heavy metals through feed contamination. From a nutritional viewpoint, poultry feeds need to be critically formulated. Adv. Vet. Anim. Res., 11(1): 47-54, March 2024 http://doi.org/10.5455/javar.2024.k746